Nano modified epoxy powder coating and preparation method thereof

By combining imidazole curing accelerators with nano-fillers and modifying nano-SiO2 and TiO2 with phenylsilane coupling agents, nano-modified epoxy powder coatings were prepared, solving the problems of weather resistance and high-temperature curing of epoxy powder coatings, and achieving low-temperature rapid curing and improved anti-corrosion performance.

CN120904757AActive Publication Date: 2025-11-07TYHOO CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202511404831.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-29
Publication Date
2025-11-07
Estimated Expiration
2045-09-29

AI Technical Summary

Technical Problem

Epoxy powder coatings have poor weather resistance under outdoor sunlight, high-temperature curing limits their application, and the coating is prone to developing holes and cracks, leading to a decrease in corrosion resistance.

Method used

By combining imidazole curing accelerators with nano-fillers and modifying the surface of nano-SiO2 and TiO2 with phenylsilane coupling agents, nano-modified epoxy powder coatings are prepared, achieving low-temperature rapid curing and improving corrosion resistance and weather resistance.

Benefits of technology

It cures rapidly at low temperatures to form a hard coating, which significantly improves the coating's corrosion resistance and UV resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_4
    Figure SMS_4
  • Figure SMS_5
    Figure SMS_5
  • Figure QLYQS_1
    Figure QLYQS_1
Patent Text Reader

Abstract

The invention relates to the technical field of epoxy powder coatings, and discloses a nano modified epoxy powder coating and a preparation method thereof. The preparation method specifically comprises the following steps: synthesizing two new phenyl silane coupling agents containing imidazole derivatives; the phenyl silane coupling agent is used as surface modification of a nanocrystallization filler (the nanocrystallization filler is formed by compounding nano-SiO2 with a corrosion-resistant function and rutile type nano-TiO2 with an excellent ultraviolet shielding effect), and a curing promotion type nanocrystallization filler with a low-temperature curing function is prepared. The filler, epoxy resin, a curing agent, a pigment, a filler and an auxiliary agent are subjected to premixing, melt extrusion, cooling crushing, grinding and sieving processes, and the nano modified epoxy powder coating is prepared. The nano modified epoxy powder coating prepared by the invention can be quickly cured at 160 DEG C or below, and the coating obtained by curing shows excellent corrosion resistance and weather resistance.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of epoxy powder coating, in particular to a nano-modified epoxy powder coating and a preparation method thereof. BACKGROUND

[0002] The epoxy powder coating is a solid powder coating composed of epoxy resin, curing agent, pigment, filler and additive, which is prepared by pre-mixing, melt extrusion, cooling, crushing, grinding and sieving. The coating is uniformly attached to the surface of metal (such as low carbon steel) by electrostatic spraying or fluidized bed dipping, and is cured to form a hard and durable coating under heating, thereby protecting the metal from corrosion.

[0003] Since the molecular structure of epoxy resin contains aromatic ether bonds which are easily degraded by ultraviolet light, oxidation and molecular chain rupture will occur under the irradiation of outdoor sunlight (especially UV ultraviolet light). In addition, the epoxy system (such as dicyandiamide curing) usually needs to be cured at a high temperature of 180-200℃ for 10-15 minutes, which not only consumes a lot of energy, but also limits its application on heat-sensitive substrates (such as some plastics, pre-assembled parts, electronic components). Therefore, the epoxy powder coating has inherent defects of poor weather resistance and high curing temperature.

[0004] In addition, after the epoxy resin is cured, defects such as pores and cracks are easily generated in the coating, so that corrosive media such as water and oxygen can penetrate into the epoxy resin through these small pores, thereby destroying the corrosion resistance of the coating and accelerating the corrosion of the metal.

[0005] It has been found that the epoxy powder coating prepared by using 3-glycidoxypropyltrimethoxysilane modified silica nanoparticles as filler exhibits excellent corrosion resistance. Nano-titanium dioxide has excellent ultraviolet shielding effect, which can help to improve the ultraviolet resistance of the powder coating. The addition of imidazole type accelerator can reduce the curing temperature of the dicyandiamide system and shorten the curing time.

[0006] Based on this, the present application proposes to use imidazole type curing accelerator in combination with nano-filler, so as to simultaneously achieve the technical goals of low-temperature rapid curing, improving the corrosion resistance and weather resistance of the coating. SUMMARY

[0007] The present application synthesizes a phenyl silane coupling agent containing imidazole derivative, which is modified on the surface of nano-filler to prepare a curing-promoting nano-filler. The filler, together with epoxy resin, curing agent, pigment, filler and additive, is pre-mixed, melt-extruded, cooled, crushed, ground and sieved to prepare a nano-modified epoxy powder coating. The coating can simultaneously achieve the technical goals of low-temperature rapid curing, improving the corrosion resistance and weather resistance of the coating.

[0008] To achieve the above-mentioned purposes, the present application adopts the following technical solutions: A nano-modified epoxy powder coating, comprising the following raw materials in parts by weight: 90-110 parts of epoxy resin, 3-5 parts of curing-promoting nano-filler, 2-3 parts of barium sulfate, 2-4 parts of curing agent, 1-2 parts of leveling agent, 30-40 parts of pigment, 0.4-0.6 parts of defoaming agent, 0.5-1.5 parts of polyethylene wax powder; The curing-promoting nano-filler is prepared by compounding curing-promoting nano-SiO2 and curing-promoting nano-TiO2 at a mass ratio of 2:1. The curing-promoting nano-SiO2 is prepared by surface modification of nano-SiO2 rich in hydroxyl functional groups with a phenyl silane coupling agent containing imidazole derivatives. The curing-promoting nano-TiO2 is prepared by surface modification of rutile-type nano-TiO2 rich in hydroxyl functional groups with a phenyl silane coupling agent containing imidazole derivatives. The phenyl silane coupling agent containing imidazole derivatives is phenyl silane coupling agent I or / and phenyl silane coupling agent II.

[0009] Preferably, the amount of phenyl silane coupling agent in the curing-promoting nano-SiO2 is 5wt%-15wt% of the amount of nano-silica. The amount of phenyl silane coupling agent in the curing-promoting nano-TiO2 is 5wt%-15wt% of the amount of nano-titania.

[0010] Preferably, the particle size of the nano-silica is 30-100nm.

[0011] Preferably, the particle size of the nano-titania is 30-100nm.

[0012] Preferably, the model of the epoxy resin is E-12, the curing agent is dicyandiamide, the model of the leveling agent is BYK-360P, the pigment is titanium white, and the defoaming agent is benzoin.

[0013] Preferably, the curing temperature of the epoxy powder coating is 140-160℃.

[0014] A preparation method of a nano-modified epoxy powder coating, comprising the following steps: according to the formula of the nano-modified epoxy powder coating, ingredients are prepared, the raw materials are mixed uniformly, and then the nano-modified epoxy powder coating is prepared through the processes of melt extrusion, cooling and crushing, and grinding and screening. In the melt extrusion process, the feeding temperature is set to 70-80℃, and the melt section and the discharge temperature are set to 90-110℃.

[0015] Preferably, the preparation method of the phenyl silane coupling agent I is as follows: Based on the ring-opening reaction mechanism of secondary amine-epoxy groups, 1-mole equivalent of 2-ethyl-4-methyl imidazole and 1-mole equivalent of allyl glycidyl ether are used as raw materials to prepare intermediate 1-1; Based on the silicon-hydrogen addition reaction mechanism, 1-mole equivalent of intermediate 1-1 and 1-mole equivalent of 1,1,5,5-tetramethyl-3,3-diphenyl trisiloxane are reacted to prepare intermediate 1-2; Based on the silicon-hydrogen addition reaction mechanism, 1-mole equivalent of intermediate 1-2 and 1-mole equivalent of allyl triethoxysilane are reacted to prepare phenyl silane coupling agent I.

[0016] Preferably, the preparation method of the phenyl silane coupling agent II is as follows: Based on the silicon-hydrogen addition reaction mechanism, 1-mole equivalent of intermediate 1-1 and 1-mole equivalent of 3,13-dihydrogen octaphenyl double-clam half-siloxane are reacted to prepare intermediate 2-1; By reacting the silicon-hydrogen bond of 1-mole equivalent of intermediate 2-1 with the alkyl functional group of 1-mole equivalent of allyl triethoxysilane, phenyl silane coupling agent II is prepared.

[0017] Preferably, the nano-modified epoxy powder coating is uniformly attached to the surface of solar photovoltaic supports, outdoor lamps and outdoor plastic furniture or equipment by electrostatic spraying or fluidized bed dipping, and is cured at a temperature of 140-160 DEG C to form a hard and durable coating.

[0018] The present application has the following advantages: Based on the molecular design mechanism, two new phenyl silane coupling agents containing imidazole derivatives are synthesized, the phenyl silane coupling agent is used as the surface modification of nano-filler (the nano-filler is composed of nano-SiO2 with corrosion-resistant function and rutile nano-TiO2 with excellent ultraviolet shielding effect), a curing-promoting nano-filler with low-temperature curing function is prepared, and the hydroxyl groups and benzene ring structure contained on the surface of the filler can improve the compatibility of the nano-filler and the epoxy resin; The curing-promoting nano-filler is used as a functional modified filler of the epoxy powder coating to prepare a nano-modified epoxy powder coating. The experimental results prove that the nano-modified epoxy powder coating prepared by the present application can be rapidly cured below 160 DEG C, and the coating obtained by curing exhibits excellent corrosion resistance and weather resistance. DETAILED DESCRIPTION Example 1:

[0019] The synthesis process of the phenyl silane coupling agent I is as follows: The first step: through the ring opening reaction of 1 mole equivalent of the secondary amine functional group of 2-ethyl-4-methyl imidazole and 1 mole equivalent of the epoxy group of allyl glycidyl ether, an intermediate 1-1 is generated; The second step: through the reaction of 1 mole equivalent of the alkenyl functional group of the intermediate 1-1 and 1 mole equivalent of the silicon-hydrogen bond of 1,1,5,5-tetramethyl-3,3-diphenyl trisiloxane, an intermediate 1-2 is generated; The third step: through the reaction of 1 mole equivalent of the silicon-hydrogen bond of the intermediate 1-2 and 1 mole equivalent of the alkenyl functional group of allyl triethoxysilane, a phenyl silane coupling agent I is generated; The experimental steps of the phenyl silane coupling agent I are as follows: Step one: 2.21 g of 2-ethyl-4-methyl imidazole is added to a reaction container, 30 mL of dimethylbenzene is added, after the addition, the temperature is raised to 120℃, after stirring to dissolve, 2.3 g of allyl glycidyl ether is added, and the reaction is continued at 120℃ for 2 h, and then the temperature is reduced to room temperature, the solvent is removed by reduced pressure distillation, and vacuum drying is carried out at 60℃ for 10 h to prepare the intermediate 1-1; Step two: 2.25 g of the intermediate 1-1, 3.34 g of 1,1,5,5-tetramethyl-3,3-diphenyl trisiloxane and 40 mL of N,N-dimethylformamide are added to a 250 mL four-necked flask equipped with a stirrer, a thermometer, a reflux condenser and a nitrogen inlet tube, and then nitrogen is introduced, heating and stirring are carried out, the temperature is raised to 70℃, 1 mL of chloroplatinic acid isopropanol solution (0.02 g / mL) is added dropwise, after the dropwise addition is completed, the reaction is carried out at 90℃ for 5 h, after the reaction is completed, the solvent is removed by reduced pressure distillation, washing is carried out, and vacuum drying is carried out to prepare the intermediate 1-2; Step three: under the protection of nitrogen, 5.57 g of the intermediate 1-2 and 2.05 g of allyl triethoxysilane are added to 50 mL of N,N-dimethylformamide, mechanical stirring is carried out until they are uniform, the temperature is raised to 70℃, 2 mL of chloroplatinic acid isopropanol solution (0.02 g / mL) is added dropwise, after the dropwise addition is completed, the temperature is raised to 90℃, and the reaction is carried out for 5 h, the solvent is removed by reduced pressure distillation, and vacuum drying is carried out at 60℃ until the weight is constant to prepare the phenyl silane coupling agent I; The chemical structural formula of the phenyl silane coupling agent I is as follows: ; The nuclear magnetic resonance hydrogen spectrum of the phenyl silane coupling agent I is as follows: 1H NMR (DMSO-d6, 400 MHz) δ: 0.08 (s, 12H), 0.68-0.88 (m, 6H), 1.17-1.19 (t, 9H), 1.26-1.29 (t, 3H), 1.37-1.45 (m, 2H), 1.52-1.59 (m, 2H), 2.29 (s, 3H), 2.74-2.78 (m, 2H), 3.34-3.41 (m, 2H), 3.45-3.54 (m, 2H), 3.77-3.82 (m, 6H), 3.88-3.98 (m, 2H), 4.05-4.06 (d, 1H), 4.11-4.17 (m, 1H), 6.83 (s, 1H), 7.23-7.26 (t, 4H), 7.34-7.37 (t, 2H), 7.46-7.47 (d, 4H). Example Two:

[0020] Synthesis of phenylsilane coupling agent II, the synthesis process is as follows: First step: through 1 mole equivalent of the alkenyl functional group of intermediate 1-1 and 1 mole equivalent of the silicon hydrogen bond of 3,13-dihydrooctaphenyl disilsequioxane (DDSQ-H) reaction, to generate intermediate 2-1; Second step: through 1 mole equivalent of the silicon hydrogen bond of intermediate 2-1 and 1 mole equivalent of the alkenyl functional group of allyl triethoxysilane reaction, to generate phenylsilane coupling agent II; The experimental steps of phenylsilane coupling agent II are as follows: Step one: add 100 mL of isopropyl alcohol, 2.84 g of deionized water and 2.85 g of sodium hydroxide into a 250 mL three-necked flask under nitrogen protection, stir uniformly, then continue to add 21.24 g of phenyltrimethoxysilane, reflux at 80℃ for 4 h, then cool to room temperature, continue to react for 15 h, after the reaction is completed, rotary evaporation to obtain white solid, dry in a 40℃ vacuum oven for 6 h, to obtain octaphenylcyclotetrasiloxane sodium silanolate; Under nitrogen protection, add 11.24 g of octaphenylcyclotetrasiloxane sodium silanolate and 2.94 mL of triethylamine into 100 mL of anhydrous tetrahydrofuran, stir under ice bath, add 10 mL of tetrahydrofuran solution containing 3.42 g of methyldichlorosilane, react at 0℃ for 4 h, then continue to react at room temperature for 20 h, after the reaction is completed, remove the solvent by rotary evaporation, wash, and dry at 60℃ under vacuum for 7 h, to prepare 3,13-dihydrooctaphenyl disilsequioxane (DDSQ-H); Step two: 5.77 g of 3,13-dihydro-octaphenylsilsesquibiphenyl, 1.12 g of intermediate 1-1 and 50 mL of toluene were added into a 100 mL flask under nitrogen protection, 1 mL of chloroplatinic acid isopropanol solution (0.02 g / mL) was added dropwise under stirring, and the reaction was carried out at 80°C for 24 h. After the reaction was completed, the solvent was removed by rotary evaporation to obtain intermediate 2-1; Step three: 6.9 g of intermediate 2-1 and 1.1 g of allyl triethoxysilane were added into 50 mL of toluene, and the mixture was stirred mechanically. 1 mL of chloroplatinic acid isopropanol solution (0.02 g / mL) was added dropwise, and the temperature of the system was raised to 80°C. The reaction was carried out for 24 h, and the solvent was removed by rotary evaporation. The product was washed and dried at 60°C under vacuum for 8 h to obtain phenyl silane coupling agent II; The chemical structural formula of phenyl silane coupling agent II is as follows: ; In the formula, R is a phenyl group, and the chemical structure is as follows: ; The H NMR spectrum of phenyl silane coupling agent II is as follows: 1 H NMR (DMSO-d6, 400 MHz) δ: 0.11 (s, 6H), 0.70-0.82 (m, 2H), 0.90-0.94 (t, 2H), 1.01-1.16 (m, 2H), 1.23-1.26 (t, 9H), 1.36-1.39 (t, 3H), 1.48-1.56 (m, 2H), 1.60-1.69 (m, 2H), 2.29 (s, 3H), 2.74-2.78 (m, 2H), 3.40-3.43 (t, 2H), 3.48-3.57 (m, 2H), 3.77-3.82 (m, 6H), 3.90-4.00 (m, 2H), 4.08-4.09 (d, 1H), 4.14-4.20 (m, 1H), 6.83 (s, 1H), 7.27-7.34 (m, 24H), 7.50-7.55 (m, 16H). Example three:

[0021] (1) The curing-promoting nano-SiO2 was prepared by surface modification of nano-SiO2 (average particle size 50 nm) rich in hydroxyl functional groups on the surface with phenyl silane coupling agent; The curing-promoting nano-SiO2 specifically includes curing-promoting nano-SiO2 (I), curing-promoting nano-SiO2 (II) and curing-promoting nano-SiO2 (I+II); The method for preparing the curing-promoting nano-SiO2(I) comprises the following steps: 10 g of nano-SiO2 (average particle size: 50 nm) is added into 100 mL of an ethanol solution (ethanol: water = 19:1 in mass ratio), and then uniformly mechanically stirred; 1.2 g of phenyl silane coupling agent I is added; after the addition is completed, the temperature of the system is increased to 110°C, and the system is condensed and refluxed for reaction for 3 h; after the temperature is decreased to room temperature, filtration, washing and vacuum drying at 50°C for 8 h are performed to obtain the curing-promoting nano-SiO2(I); The method for preparing the curing-promoting nano-SiO2(II) is different from the method for preparing the curing-promoting nano-SiO2(I) only in that 1.2 g of phenyl silane coupling agent II is used to replace the 1.2 g of phenyl silane coupling agent I; The method for preparing the curing-promoting nano-SiO2(I+II) is different from the method for preparing the curing-promoting nano-SiO2(I) only in that 0.6 g of phenyl silane coupling agent I and 0.6 g of phenyl silane coupling agent II are used to replace the 1.2 g of phenyl silane coupling agent I; (2) The curing-promoting nano-TiO2 is prepared by surface modification of the rutile-type nano-TiO2 (average particle size: 50 nm) rich in hydroxyl functional groups on the surface through a phenyl silane coupling agent; The curing-promoting nano-TiO2 specifically comprises curing-promoting nano-TiO2(I), curing-promoting nano-TiO2(II) and curing-promoting nano-TiO2(I+II); The method for preparing the curing-promoting nano-TiO2(I) comprises the following steps: 10 g of rutile-type nano-TiO2 (average particle size: 50 nm) is added into 100 mL of an ethanol solution (ethanol: water = 19:1 in mass ratio), and then uniformly mechanically stirred; 1.2 g of phenyl silane coupling agent I is added; after the addition is completed, the temperature of the system is increased to 110°C, and the system is condensed and refluxed for reaction for 3 h; after the temperature is decreased to room temperature, filtration, washing and vacuum drying at 50°C for 8 h are performed to obtain the curing-promoting nano-TiO2(I); The method for preparing the curing-promoting nano-TiO2(II) is different from the method for preparing the curing-promoting nano-TiO2(I) only in that 1.2 g of phenyl silane coupling agent II is used to replace the 1.2 g of phenyl silane coupling agent I; The method for preparing the curing-promoting nano-TiO2(I+II) is different from the method for preparing the curing-promoting nano-TiO2(I) only in that 0.6 g of phenyl silane coupling agent I and 0.6 g of phenyl silane coupling agent II are used to replace the 1.2 g of phenyl silane coupling agent I; (3) The curing-promoting nano-filler is prepared by compounding curing-promoting nano-SiO2 and curing-promoting nano-TiO2 according to a mass ratio of 2:1, and the compounded filler includes: curing-promoting nano-filler (I), curing-promoting nano-filler (II), and curing-promoting nano-filler (I+II), and the specific formula is shown in Table 1 below. Table 1 Formula of curing-promoting nano-filler Example Four:

[0022] (1) The nano-modified epoxy powder coating I is prepared from the following raw materials: E-12 bisphenol A type epoxy resin (model 604), 100 parts by weight; Curing-promoting nano-filler (I), 4 parts by weight; Barium sulfate, 2.5 parts by weight; Dicyandiamide curing agent, 3 parts by weight; Leveling agent (model BYK-360P), 1.5 parts by weight; Titanium white, 35 parts by weight; Benzooin, 0.5 parts by weight; Polyethylene wax powder, 1 part by weight; The preparation method of the nano-modified epoxy powder coating I includes the following steps: According to the formula of the nano-modified epoxy powder coating I, the E-12 bisphenol A type epoxy resin, the dicyandiamide curing agent, the leveling agent, the titanium white, the benzooin, and the polyethylene wax powder are mixed, and then the curing-promoting nano-filler I is added. After being fully mixed, the mixture is fed into a double-screw extruder, the feeding temperature is set to 75°C, and the melting section and the discharging temperature are set to 100°C. The extruded material is ground into powder by a grinder, and then sieved through a 160-mesh sieve to obtain the nano-modified epoxy powder coating I.

[0023] (2) The nano-modified epoxy powder coating II is prepared by replacing the curing-promoting nano-filler (I) with the curing-promoting nano-filler (II) in the nano-modified epoxy powder coating I.

[0024] (3) The nano-modified epoxy powder coating III is prepared by replacing the curing-promoting nano-filler (I) with the curing-promoting nano-filler (I+II) in the nano-modified epoxy powder coating I. Performance test:

[0025] I. Gel time: according to the standard of GB / T 16995-1997 "Determination of gel time of thermosetting powder coatings at a given temperature", 0.25 mL of nano-modified epoxy powder coating is measured and placed on a preheated test plate with a temperature of 140℃, 160℃, and when the powder on the test plate just melts, start timing, at this time, use a needle with low heat capacity to stir a small circle on the melted powder, every 2-3 seconds, use a needle to lift the melted powder about 1 cm upwards, when the silk formed by lifting the powder becomes brittle and breaks or cannot be lifted out of the melted powder, stop timing, the time recorded at this time is the gel time of the powder coating; II. Dry sandpaper grinding is used to polish the 120mm×50mm tinplate sheet, and after ensuring that the original surface layer is completely removed, the surface residual substances are wiped clean with acetone and dried for standby; The nano-modified epoxy powder coating prepared by the application is uniformly sprayed on the treated tinplate sheet using an electrostatic spraying device, and is cured at 160℃ for 20min to prepare a coating sample with a thickness of 100μm; (1) Impact resistance: according to the standard of GB / T 1732-2020 "Paint film impact resistance test method", the positive impact height and the reverse impact height of the coating sample are tested; (2) UV resistance test: the coating sample is placed in a UV aging oven for aging treatment, the temperature is 50℃, 8 UV-B irradiation, the irradiation light intensity is 0.68W / m 2 , the sample is taken out after irradiation for 48h and 144h respectively, and the gloss of the coating sample is measured using a gloss meter; (3) Corrosion resistance test: according to the standard of HG / T 2006-2022 "Thermosetting and thermoplastic powder coatings", the alkali resistance, acid resistance and salt spray resistance of the coating sample are tested; The test results are shown in Table 2 below; Table 2 Performance test results of nano-modified epoxy powder coating

[0026] The difference between the comparative example and the nano-modified epoxy powder coating I is only that no curing-promoting nano filler (I) is added; From the test results, it can be seen that the nano-modified epoxy powder coating prepared by the application can realize low-temperature rapid curing, and the coating obtained after curing has significantly improved beneficial technical effects in terms of corrosion resistance and UV resistance.

Claims

1. A nano-modified epoxy powder coating, characterized in that, The raw materials include the following weight parts: 90-110 parts of epoxy resin, 3-5 parts of curing-promoting nano-filler, 2-3 parts of barium sulfate, 2-4 parts of curing agent, 1-2 parts of leveling agent, 30-40 parts of pigment, 0.4-0.6 parts of defoaming agent, and 0.5-1.5 parts of polyethylene wax powder; The curing-promoting nano-filler is prepared by compounding curing-promoting nano-SiO2 and curing-promoting nano-TiO2 at a mass ratio of 2:1; The curing-promoting nano-SiO2 is prepared by surface modification of nano-SiO2 rich in hydroxyl functional groups with phenyl silane coupling agent containing imidazole derivatives; The curing-promoting nano-TiO2 is prepared by surface modification of rutile-type nano-TiO2 rich in hydroxyl functional groups with phenyl silane coupling agent containing imidazole derivatives; The phenyl silane coupling agent containing imidazole derivatives is phenyl silane coupling agent I or / and phenyl silane coupling agent II; The chemical structural formula of the phenyl silane coupling agent I is as follows: ; The chemical structural formula of the phenyl silane coupling agent II is as follows: ; wherein R is a phenyl group having the chemical structure .

2. The nano-modified epoxy powder coating according to claim 1, characterized in that, The amount of the phenyl silane coupling agent in the curing-promoting nano-SiO2 is 5wt%-15wt% of the amount of nano-silica; The amount of the phenyl silane coupling agent in the curing-promoting nano-TiO2 is 5wt%-15wt% of the amount of nano-titania.

3. The nano-modified epoxy powder coating according to claim 2, characterized in that, The particle size of the nano-silica is 30-100nm.

4. The nano-modified epoxy powder coating according to claim 2, characterized in that, The particle size of the nano-titania is 30-100nm.

5. The nano-modified epoxy powder coating according to claim 1, characterized in that, The model of the epoxy resin is E-12, the curing agent is dicyandiamide, the model of the leveling agent is BYK-360P, the pigment is titanium white, and the defoaming agent is benzoin.

6. The nano-modified epoxy powder coating according to claim 1, characterized in that, The curing temperature of the epoxy powder coating is 140-160℃.

7. The method for preparing a nano-modified epoxy powder coating according to claim 1, characterized in that, The method comprises the following steps: According to the formula of the nano-modified epoxy powder coating, the raw materials are mixed uniformly, and then the nano-modified epoxy powder coating is prepared through the processes of melting extrusion, cooling crushing and grinding screening; The feeding temperature in the process of melting extrusion is set to 70-80℃, and the melting section and the discharging temperature are set to 90-110℃.

8. The method for preparing a nano-modified epoxy powder coating according to claim 7, characterized in that, The preparation method of the phenyl silane coupling agent I is as follows: Based on the ring-opening reaction mechanism of secondary amine-epoxy groups, 1 mole equivalent of 2-ethyl-4-methyl imidazole and 1 mole equivalent of allyl glycidyl ether are used as raw materials to prepare intermediate 1-1; Based on the silicon-hydrogen addition reaction mechanism, 1 mole equivalent of intermediate 1-1 reacts with 1 mole equivalent of 1,1,5,5-tetramethyl-3,3-diphenyl trisiloxane to prepare intermediate 1-2; Based on the silicon-hydrogen addition reaction mechanism, 1 mole equivalent of intermediate 1-2 reacts with 1 mole equivalent of allyl triethoxysilane to prepare the phenyl silane coupling agent I.

9. The method for preparing a nano-modified epoxy powder coating according to claim 7, characterized in that, The preparation method of the phenyl silane coupling agent II is as follows: Based on the silicon-hydrogen addition reaction mechanism, 1 mole equivalent of intermediate 1-1 reacts with 1 mole equivalent of 3,13-dihydrooctaphenyl bis-clam plate silsesquioxane to prepare intermediate 2-1; The phenyl silane coupling agent II is prepared by reacting 1 mole equivalent of the silicon-hydrogen bond of the intermediate 2-1 with 1 mole equivalent of the alkenyl functional group of allyl triethoxysilane.

10. The nano-modified epoxy powder coating according to claim 1, characterized in that, The nano-modified epoxy powder coating is uniformly attached to the surface of solar photovoltaic support, outdoor lamps and lanterns and outdoor plastic furniture or equipment by electrostatic spraying or fluidized bed dipping, and a hard and durable coating is formed by curing at a temperature of 140-160 DEG C.

Citation Information

Patent Citations

  • Low-temperature fast-curing epoxide powder paint and preparation method thereof

    CN103666203A

  • Special epoxy powder coating for thick-coated steel strand

    CN106752722A

  • Low-temperature curing powder coating as well as preparation method and application thereof

    CN107674540A

  • Fast-curing polyester powder coating and preparation method thereof

    CN110229591A

  • Epoxy resin powder coating

    JP2008056838A